Effect of Adding Flax Seed to Bread Flour which Produced in the Laboratory and Study its Quality Properties - Ibtihal I. M (Journal of Global Pharma Technology, 2016)
The aim of this current research was to Knowledge effect of addition of Flax seed at different percentages to bread flour and pop loaf bread was prepared that addition 10 % from Flax seed flour to bread flour resulting in increasing the percentages of moisture, ash, fat, fiber and protein. The result showed no significant differences in the moisture content, low value of gluten content and falling number. Was noticed in all treatment. Specific volume, it is the same for all treatments. Sensory evaluations of loaf bread appear no significant difference between control 100 % wheat flour and 10 % Flax seed. And found that the bread of both types was acceptable. Therefore this conclusion we can point out that the Flax seed can be used with the flour to prepare the flat bread. To improve the deffency of gluten.Keyword: Bread, Flax seed, Gluten, Fiber.